DEVELOPMENT OF LABORATORY SCALE NEAR SHORE WATER LEVEL MEASURING SYSTEM FOR TSUNAMI EARLY DETECTION - Awaludin Salam, Rahmat
Tsunami is one of the hazardous disasters that have a destructive characteristic. It has been reported that there are 66% of the live lost caused by natural disasters was caused by tsunami and Asia, especially Indonesia, is area which gave a big contribution on it. The occurrence of tsunami was induced by the vibration around the sea plate. Until this time, sea crust earthquake was the main cause of tsunami occurrence. The condition of Indonesia region which is in the region of three active plate subduction making Indonesia as one of the countries with high possibility of tsunami occurrence. This is supported by reports from BNPB which indicating a high incidence and casualties caused by the tsunami in Indonesia. Besides, based on the world tsunami history, the tsunami caused by Krakatau eruption and Aceh’s tsunami are two of three biggest tsunami incidence Tsunami around the worl which contribute to the high of life lost. Therefore, a real time tsunami detection system which can warn the society around the coastline immediately is urgently needed. Tsunami incidence is usually started by the sudden change of sea water level. This change is a parameter that usually used as parameter for developing the establish tsunami early warning systems. High accuracy and real time monitoring are the indicators for developing a robust tsunami early warning system so that the victims of this disasters can be reduced significantly. The infrequent of tsunami occurrence cause the less of efficiency of the eastablish warning systems. Besides, the high cost of production as well as care for the development of early warning systems are its own problems. Therefore, an economics early warning system with the effective reading the parameters and also the efficient system utilization is required to be developed. One of the systems that could be used and developed is a tide gauge based local tsunami early warning system which has an easiness on developing and maintaining, and also a near real time ability on detecting the tsunami incidence. Based on the described backgrounds, on the dissertation research that was conducted, a tide gauge based local water level measuring system has been developed. The monitoring system is developed using the use of pressure sensor and ultrasonic sensor as sea water level measurer with will be equipped with the vibration detector based on accelerometer to detect the incidence of earthquake around the system; some detection of environmental parameters such as temperature, humidity and solar intensity; and also the power management to control the optimal electrical power. The development of power management system become an important part on early warning system since the system usually away from the power line. In addition, on this research, to complete the sea water level monitoring results, a tide prognosis has to be made as a comparison to the reading resulted by the system. From this research, a sea water level as tsunami local early warning system is hopefully can read the water level caused by the tide which appropriate with the made tide prognosis. Besides, power management on the system can play a good role on controlling the input or output of electrical power. With this research, hopefully the tsunami occurrence can be detected well so that the victims of this disasters, can be reduced significantly. To test the system's ability to detect the changes in water level of a wave, in this study a wave simulator system was also developed based on artificial wave simulation. The developed wave simulator system is successfully provided the simulation of artificial waves which its wave height and frequency are independent to each other. By using a wave simulator system and wave flume, the water level measurement system is then tested for its dynamic characteristics. The results show that the system is able to produce water level readings in accordance with the wave gauge or the water level meter embedded in the simulator system and the wave flume. Not only the wave height, the frequency of the waveform that is read by the system corresponds to the simulated frequency. Thus, the water level measurement system can be used to measure changes in wave water level which is further used as a detection of tsunami events.